Rheumatoid Arthritis and Cardiovascular Risk: Retrospective Matched-Cohort Analysis Based on the RECORD Study of the Italian Society for Rheumatology - Argnani, Lisa; Zanetti, Anna; Carrara, Greta; Silvagni, Ettore; Guerrini, Giulio; Zambon, Antonella; Scirè, Carlo Alberto (Frontiers in Medicine, 2021)
Background: Rheumatoid arthritis (RA) is associated with an increase in cardiovascular (CV) risk. This issue maybe not only explained by a genetic component, as well as by the traditional CV risk factors, but also by an underestimation and undertreatment of concomitant CV comorbidities. Method: This was a retrospective matched-cohort analysis in the Italian RA real-world population based on the healthcare-administrative databases to assess the CV risk factors and incidence of CV events in comparison with the general population. Persistence and adherence to the CV therapy were also evaluated in both groups. Results: In a RA cohort (N = 21,201), there was a greater prevalence of hypertension and diabetes with respect to the non-RA subjects (N = 249,156) (36.9 vs. 33.4% and 10.2 vs. 9.6%, respectively), while dyslipidemia was more frequent in the non-RA group (15.4 vs. 16.5%). Compared with a non-RA cohort, the patients with RA had a higher incidence of atrial fibrillation (incidence rate ratio, IRR 1.28), heart failure (IRR 1.53), stroke (IRR 1.19), and myocardial infarction (IRR 1.48). The patients with RA presented a significantly lower persistence rate to glucose-lowering and lipid-lowering therapies than the controls (odds ratio, OR 0.73 [95% CI 0.6–0.8] and OR 0.82 [0.8–0.9], respectively). The difference in the adherence to glucose-lowering therapy was significant (OR 0.7 [0.6–0.8]), conversely no statistically significant differences emerged regarding the adherence to lipid-lowering therapy (OR 0.89 [95% CI 0.8–1.0]) and anti-hypertensive therapy (OR 0.96 [95% CI 0.9–1.0]). Conclusion: The patients with RA have a higher risk of developing CV events compared with the general population, partially explained by the excess and undertreatment of CV risk factors.